Compliance of St Joseph’s Hospital Roma, Lesotho with the National Tuberculosis Programme of Lesotho, 2007 and 2008 - Oladoyinbo O. Samuel; Pierre J.T. de Villiers (African Journal of Primary Health Care & Family Medicine, 2014)
Background: In 2009 Lesotho had an estimated TB prevalence of 696 cases/100 000 population − the 4th highest in the world. This epidemic was characterised by high rates of death, treatment failure and unknown treatment outcomes. These adverse outcomes were attributable to a high rate of TB and/or HIV co-infection and weaknesses in the implementation of Lesotho’s National Tuberculosis Programme (NTP). This study was conducted in St Joseph’s Hospital, Roma (SJHR) to assess the implementation of the NTP. Method: Records of 993 patients entered into the SJHR TB register between 2007 and 2008 were reviewed. Patients’ treatment details were extracted from the register, validated and analysed by STATA 10.0. Results: Of 993 patients registered: 88% were new patients, 37% were diagnosed on sputum smear microscopy alone, 35% were diagnosed on sputum smear microscopy with chest X-ray, whilst 25% were diagnosed on chest X-ray alone. In addition: 33% were sputum smear positive, 45% were sputum smear negative, and 22% had extra-pulmonary TB. As to treatment outcome: 26% were cured, 51% completed treatment, and 51% converted from sputum smear positive to sputum smear negative over six months, whilst 16% died. Regarding HIV, 77% of patients were tested for HIV and 59% had TB and/or HIV co-infection. Of ten NTP targets only the defaulter and treatment failure rate targets were met. Conclusion: Whilst only two out of ten NTP targets were met at SJHR in 2007–2008, improvements in TB case management were noted in 2008 which were probably due to the positive effects of audit on staff performance.